Sinonasal Undifferentiated Carcinoma (SNUC): From an Entity to Morphologic Pattern and Back Again-A Historical Perspective - Agaimy, Abbas; Franchi, Alessandro; Lund, Valerie J.; Skalova, Alena; Bishop, Justin A.; Triantafyllou, Asterios; Andreasen, Simon; Gnepp, Douglas R.; Hellquist, Henrik; Thompson, Lester D. R.; Rinaldo, Alessandra; Ferlito, Alfio (Advances in Anatomic Pathology, 2020)
Plasmablastic neoplasms encompass several entities including plasmablastic lymphoma, plasmablastic plasmacytoma/multiple myeloma, primary effusion lymphoma and its extracavitary variant, anaplastic lymphoma kinase-positive large B-cell lymphoma, and Kaposi sarcoma-associated herpesvirus/human herpesvirus 8 (HHV8)-positive diffuse large B-cell lymphoma, not otherwise specified. Morphologically, the tumor cells are large with eccentrically located nuclei, prominent nucleoli, and basophilic/amphophilic cytoplasm. Immunophenotypically, the tumor cells express plasma cell-related antigens including CD38, CD138, interferon regulatory factor-4 (IRF4)/MUM1, PR domain zinc finger protein-1 (PRDM1), and/or X-box binding protein-1 (XBP1), with frequent loss of CD20. These tumors are diagnostically challenging for general pathologists due to their overlapping morphology and immunophenotype, and due to their rarity, and particularly so when clinical and radiologic information is insufficient. We also discuss HHV8-negative effusion-based lymphoma due to its overlapping features with primary effusion lymphoma. In this review, we focus on the useful diagnostic markers and pertinent molecular findings in these distinct entities and propose a practical diagnostic algorithm using anaplastic lymphoma kinase, HHV8, in situ hybridization for Epstein-Barr virus-encoded small RNA, immunoglobulin M, light chain stains, and clinicoradiologic criteria to avoid misdiagnosis. At the molecular level, MYC protein overexpression with or without MYC rearrangement and PRDM1-inactivating mutations or deletions are noted in a subset of such tumors, especially in plasmablastic lymphoma. Prognosis in these entities is dismal with conventional CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) chemotherapy. Therefore, novel target therapies, such as anti-CD30 agents, and/or immune blockade therapy, are potential treatment options in the future.
CRIS-Team Scopus Importer:2020-02-28
Keywords: ALK-positive large B-cell lymphoma; effusion-based lymphoma; Epstein-Barr virus; HHV8-positive diffuse large B-cell lymphoma; human herpesvirus 8; MYC; plasmablastic lymphoma; plasmablastic plasmacytoma/multiple myeloma; PRDM1; Primary effusion lymphoma